Urban arborization management plan: tool design for efficiency and public safety - Carvalho, Joema; Maranho, Leila Teresinha (Ciência e Natura, 2022)
The inventory of the urban arborization of Positivo University parking lots in Ecoville Campus was conducted through census criteria, concerning the surroundings conflicts related to tree health, origin and phenology, that were scored and weighted. There were 393 individuals, 12 species and five families where 60% were native to Brazil. The main canopy criteria was the reaching branches on the access road in a proportion of 40%; in the trunk analysis, it was observed lesion (45%) and rot (40%); at the base’s analysis it was verified injury (43%) and root damage (35%) and exposed root (25%). The presence of fruit (26%) was higher than the flowering. Handroanthus albus presented the best result for the criteria, unlike Anadenanthera macrocarpa and Tipuana tipu. The trees showed a landscaping potential, however, the space available for the large size ones was not adequate and the large size species intensified the conflicts, when there was no planning. The species characteristics should be observed, in relation to the three-dimensional space availability. Thus, future conflicts that can be avoided endanger tree health, urban infrastructure and residents which can lead to economic losses. For this reason, the elaboration of the Municipal Urban Arborization Plan is considered primordial.